Does the Finnish intervention prevent obstetric anal sphincter injuries? A systematic review of the literature. Issue 9 (14th September 2015) - Poulsen, Mette Østergaard; Madsen, Mia Lund; Skriver-Møller, Anne-Cathrine; Overgaard, Charlotte
Abstract : Objectives: A rise in obstetric anal sphincter injuries (OASIS) has been observed and a preventive approach, originating in Finland, has been introduced in several European hospitals. The aim of this paper was to systematically evaluate the evidence behind the 'Finnish intervention'. Design: A systematic review of the literature conducted according to the Preferred Reporting for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Outcome measures: The primary outcome was OASIS. Secondary outcomes were (perinatal): Apgar scores, pH and standard base excess in the umbilical cord, and (maternal): episiotomy, intact perineum, first and second-degree perineal lacerations, duration of second stage, birth position and women's perceptions/birth experiences. Methods: Multiple databases (Cochrane, Embase, Pubmed and SveMed) were systematically searched for studies published up to December 2014. Both randomised controlled trials and observational studies were eligible for inclusion. Studies were excluded if a full-text article was not available. Studies were evaluated by use of international reporting guidelines (eg, STROBE). Results: Overall, 1042 articles were screened and 65 retrieved for full-text evaluation. Seven studies, all observational and with a level of evidence at 2c or lower, were included and consistently reported a significant reduction in OASIS. All evaluated episiotomy and found a significant increase. Three studies evaluated perinatal outcomes and reported conflicting results. No study reported on other perineal outcomes, duration of the second stage, birth positions or women's perceptions. Conclusions: A reduction in OASIS has been contributed to the Finnish intervention in seven observational studies, all with a low level of evidence. Knowledge about the potential perinatal and maternal side effects and women's perceptions of the intervention is extremely limited and the biological mechanisms underlying the Finnish intervention are not well documented. Studies with a high level of evidence are needed to assess the effects of the intervention before implementation in clinical settings can be recommended.